2020
DOI: 10.1002/kin.21391
|View full text |Cite
|
Sign up to set email alerts
|

Ambident electrophilicity of 4‐nitrobenzochalcogenadiazoles: Kinetic studies and structure‐reactivity relationships

Abstract: The kinetics of the reactions of 4‐nitrobenzofurazane 1a, 4‐nitrobenzothiadiazole 1b, and 4‐nitrobenzoselenadiazole 1c with a series of 4‐Y‐substituted phenoxide anions 2a‐e (Y = OMe, Me, H, Cl, and CN) in aqueous solution at 20°C were investigated photometrically. The derived second‐order rate constants (k2) have been combined with the nucleophilicity parameters values of these series of anions 2a‐e to determine the electrophilicity parameters E of electrophiles 1a‐c according to the linear free‐energy relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Figure 5 also reveals that the nitrobenzofurazans 1 and 2 exhibits of C‐5 position approximately 7 units of E higher than C−7 position, while the difference in reactivity between C‐5 and C‐7 positions of 4‐nitrobenzofurazan 6 , 20,21 as well as of 4‐nitrobenzoselenadiazole 7 21 and 4‐nitrobenzothiadiazole 8 21 is approximately 2 unit of E . The reason for this apparent disparity is not clear at this stage.…”
Section: Resultsmentioning
confidence: 92%
“…Figure 5 also reveals that the nitrobenzofurazans 1 and 2 exhibits of C‐5 position approximately 7 units of E higher than C−7 position, while the difference in reactivity between C‐5 and C‐7 positions of 4‐nitrobenzofurazan 6 , 20,21 as well as of 4‐nitrobenzoselenadiazole 7 21 and 4‐nitrobenzothiadiazole 8 21 is approximately 2 unit of E . The reason for this apparent disparity is not clear at this stage.…”
Section: Resultsmentioning
confidence: 92%
“…Details of the materials, synthetic procedures, kinetic measurements and pK a measurements. Table S1 containing the characteristics 1…”
Section: Supporting Information Availablementioning
confidence: 99%
“…We have previously reported that the 4-nitrobenzochalcogenadiazoles 4, [1][2][3] the 7-L-4-nitrobenzofurazans 5, [4][5][6] and the 2methoxy-3-X-5-nitrothiophene 6 [7][8][9] (Scheme 1) represent a class of neutral electron-deficient substrates which can be described by the experimental model based on the following three-parameter equation (1):…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogen–nitrogen heterocycles have been the subject of intensive experimental and theoretical studies due to their importance in biological processes as well as synthetic applications [1–5] . In this regard, we and others have been interested in the reactivity of a large variety of nucleophiles towards 4‐nitrobenzofurazan 1 a , [6–12] 4‐nitrobenzothiadiazole 1 b , [13,14] and 4‐nitrobenzoselenadiazole 1 c [14,15] . Recently, we have determined the second‐order rate constants (k) for the σ‐complexation reactions of 4‐nitrobenzochalcogenadiazoles 1 a – c , [7–9] and these values were used to estimate an electrophilicity parameter E for these electrophiles according to equation (1), [16–21] in which N and s N characterize the nucleophiles reactivity. logk(201.111ptnormalC)=snormalN(E4pt+4ptN) $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr {\rm log}\ {\rm k}\ (20\mskip2mu {^\circ}{\rm C})=s{_{{\rm N}}}\ (E\ +\ N)\hfill\cr}}$ …”
Section: Introductionmentioning
confidence: 99%